(untitled) (Research, Society and Development, 2021)
Introduction: The occurrence of depression in the elderly increases the risk of clinical morbidity. Thus, its early identification and the determinant conditions for the development of the disease is of fundamental importance for the diagnosis of the disease and, consequently, for the practice of Nursing Care Systematization (SAE). Objective: to identify and analyze the evidence available in the literature, regarding Nursing Care for the Elderly with Depression, in the 2015-2019 historical series. Methodology: The guiding question of the research was elaborated through the PICO strategy. After selecting the articles, the data were processed and analyzed with the aid of the IRaMuTeQ software (Interface of R pour les Analyzes Multidimensionnelles de Textes et de Questionnaires). Results: Articles were identified in relation to titles, year of publication, authors and database (Chart 1). It was noticed that 50% of the articles were removed from the BDENF database, while 16.6% articles were removed from the Medline database and 33.3% from the Web of Sience database. Conclusion: Through our study, we can identify that the participation of nursing in the treatment of elderly people with depression is extremely important both in the identification of signs and symptoms that indicate that the patient is entering a depressive process.